Study of Membrane Surface Potential with Pericardial Membrane - Singh, K.P.; K. Prajapati, Ramesh (Asian Journal of Chemistry, 2010)
Membrane surface potential was calculated using Poisson-Boltzman equation. It was observed that this equation is applicable to pericardial membrane and so this membrane falls in the category of low charged surface density. At higher concentration, the values of membrane surface potential decreased due to the greater deformation caused by increased value of transport of ions. Negative values of membrane surface potential showed that pericardial membrane is a positively charged structure. Moreover, this study also reveals that as soon as the negative value of -log C increases, the value of membrane surface potential also increases which is a symbol of decrease of ion transport across pericardial membrane when the concentration falls down. Increase in the value of membrane surface potential with decrease in concentration advocates the high sensitivity and self-surviving behaviour of heart function as this tissue is extensively used in constructing bioprosthetic heart valves.